Octodontomys gliroides (Rodentia: Octodontidae). (17th September 2018) - Pérez, M Julieta; Díaz, M Mónica
Abstract: The genus Octodontomys contains only a single species, Octodontomys gliroides (P. Gervais and d'Orbigny, 1844), the mountain degu, found in Andean and Sub-Andean regions of 3 countries, Argentina, Bolivia, and Chile, from elevations of about 1, 200–4, 400 m. This fossorial octodontid is typical of dry areas, inhabits rocky zones, and is active during the day and the first few hours of night. It is not of special conservation status, being common throughout its distribution, and is considered a species of "Least Concern."